Application of Quality Assurance Management in Boarding Schools: Implications for Final School Examination Results - Ayuhan, Ayuhan; Shofiyah, Siti; Karimah, Ummah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose–The objective of the present investigation was to scrutinize and elucidate the Quality of Boarding schools to foster the production of high-quality graduates. The study was conducted at Madrasah Aliyah Insan Cendekia Serpong and Dwiwarna Parung Senior High School. Design/methods/approach–This study utilized qualitative methodology, which involved various data collection techniques such as field observations, interviews with key informants within the school setting, document analysis, library research, and examination of prior research findings. The collected data were analyzed using various techniques including data reduction, presentation, and verification. Findings–The study findings indicate that Madrasa Aliyah Negeri Insan Cendekia Boarding School Serpong and Dwiwarna Senior High School Boarding School Parung surpassed national quality assurance benchmarks. Graduation chart data from 2012 to 2017 exhibited a positive trend in progress. Madrasa Aliyah Negeri Scholars had a 94% acceptance rate into state universities, 147 students accepted into prestigious public universities in Indonesia, four accepted into private colleges, and five being accepted into overseas institutions. Similarly, Dwiwarna high school had a 50% acceptance rate into public universities, with 39 students accepted into public universities, 42 accepted into private universities, and six accepted into foreign universities. Research implications/limitations–The study highlights the importance of quality assurance management in improving the performance of boarding schools. Future research can investigate the impact of specific quality assurance management practices on the academic outcomes of boarding schools. Originality/value–This Study provides unique insights into the impact of quality assurance management on a specific academic outcome, which can inform future research in the field of education.